2014
DOI: 10.1590/0103-6564a20133713
|View full text |Cite
|
Sign up to set email alerts
|

Consciência morfológica: que papel exerce no desempenho ortográfico e na compreensão de leitura?

Abstract: Resumo:A consciência morfológica diz respeito à habilidade para refletir sobre as menores unidades de sentido de uma língua e utilizá-las intencionalmente na estruturação e reconhecimento das palavras. São apresentados argumentos que apoiam a ideia de que no português, como em outras línguas alfabéticas, a consciência morfológica contribui tanto para a compreensão de leitura como para o desempenho. Participaram 72 alunos de 3º, 4º e 5º anos de uma escola pública (Curitiba-PR), separados em dois grupos de desem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 22 publications
4
7
0
11
Order By: Relevance
“…Children that show good results in morphological awareness tests present better results in reading tests, reading comprehension, and writing compared to children with inferior performance in morphological awareness tests. These findings contribute to the thought that, even in less opaque languages, reflection on the morphological structure of words contributes to reading and writing performance (3,4,7,8,16,18,21) . By analyzing the results of each article included in the review, positive correlations can be observed between morphological awareness tests and reading and writing skills.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Children that show good results in morphological awareness tests present better results in reading tests, reading comprehension, and writing compared to children with inferior performance in morphological awareness tests. These findings contribute to the thought that, even in less opaque languages, reflection on the morphological structure of words contributes to reading and writing performance (3,4,7,8,16,18,21) . By analyzing the results of each article included in the review, positive correlations can be observed between morphological awareness tests and reading and writing skills.…”
Section: Resultssupporting
confidence: 59%
“…The selected articles presented a great variability in tests which assessed reading and writing (18,20,21,(25)(26)(27) , and their selection was carried out according to the objective of each study. However, in the English language articles we observed a greater diversity of tests, as well as the use of instruments to control confounding variables (variables that may lead to erroneous results, if not statistically controlled, since they are related to the dependent and independent variable at the same time).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the basis for understanding an alphabetic writing system, such as the Brazilian Portuguese, is grasping the concept that written words are made up of units smaller than a syllable, which are responsible for the meaning of the word, and that these smaller units can be represented by graphic signs (Guimarães, Paula, Mota, & Barbosa, 2014;Moraes, 2008).…”
Section: Mn Sampaiomentioning
confidence: 99%
“…O destaque dado à consciência morfológica no português brasileiro tem sido ampliado nos últimos anos (Barbosa, 2013;Guimarães, 2016;Hagen, Miranda &, Mota, 2010;Migot, 2013;Mota, 2012;Mota, Paula &, Guimarães, 2014;Moura & Paula, 2013;Queiroz, 2012). A presente tese de doutorado busca justamente contribuir para a ampliação do conhecimento a respeito do desenvolvimento da consciência morfológica em um período da escolarização em que a escrita ainda não está consolidada.…”
Section: Introductionunclassified